Individual differences in autistic children's homograph reading: Evidence from Hebrew. (June 2017) - Brock, Jon; Sukenik, Nufar; Friedmann, Naama
Background and aims: On average, autistic individuals make more errors than control participants when reading aloud sentences containing heterophonic homographs—written words with multiple meanings and pronunciations. This finding is widely interpreted within the framework of "weak central coherence" as evidence for impaired sentence-level comprehension resulting in a failure to disambiguate the homograph meaning. However, consistent findings at the group level belie considerable individual variation. Our aim here was to determine whether that variation was reliable and whether it could be predicted. Methods: We developed a Hebrew version of the homograph-reading test, containing many more items than is possible in English. The test was administered to 18 native-Hebrew speaking autistic children and adolescents, along with a battery of reading and language assessments. Results: Participants with autism showed wide individual variation in performance on the homograph-reading task. Using a mixed random effects logistic regression analysis, we showed that measures of autism severity, single word reading, and single word comprehension all left reliable individual variation unaccounted for and none accounted for variation beyond that associated with the child's age. Instead, homograph reading was best predicted by performance on a picture naming task, which accounted for unique variation beyond age and each of the other predictors. Conclusions: Poor performance of autistic individuals on the English version of the homograph-reading task has until now been characterized as evidence for a comprehension deficit in autism. However, the results of the current study lead us to propose a new working hypothesis—that difficulties affecting some autistic individuals reflect impairment in the use of semantics to guide the selection of the appropriate phonological form during speech production. This hypothesis is consistent with the strong association between homograph reading and picture naming. It may also help explain the inconsistent pattern of results across studies using different measures of linguistic "central coherence." Implications: The results of this preliminary study should be replicated before firm conclusions are drawn. Nonetheless, the study serves to emphasize the importance of considering within-group as well as between-group variations in studies of autism. It also provides a worked example showing how mixed random effect analyses can be used to explore individual differences, distinguishing between genuine variation and psychometric noise.